Teacher’s Strategies in Instilling Pluralism Values Through Sociology Learning at School at The High School Level - Suyuti; Rinovian Rais; Inayatul Mutmainnah; Jusniati. H; Muhammad Rusdi (Universitas Muhammadiyah Palu, 2025)
This study aims to analyze the strategies used by Sociology teachers in instilling the values of pluralism to students at SMA Negeri 1 Cibinong. The method used in this research is a qualitative approach with interview techniques, observation, and documentation studies. The results showed that Sociology teachers at SMA Negeri 1 Cibinong implemented various strategies, such as integrating pluralism material in lesson plans and curriculum, using participatory learning methods, providing exemplary behavior, and involving students in extracurricular and cross- curricular activities that lead to strengthening tolerance attitudes. In addition, learning strategies that are contextual and based on students' social experiences also improve students' understanding and attitudes towards pluralism. This research reveals that the role of teachers is crucial in creating a dialogical space that supports learning the values of pluralism, and contributes to the formation of a more inclusive national character. Therefore, this study recommends that similar strategies be implemented in other schools to strengthen pluralism character education in Indonesia.